Failure analysis of quasi-isotropic CFRP laminates under high strain rate compression loading - R. M. Guedes (2008)
Dynamic compressive strength of quasi-isotropic fiber composite is investigated experimentally and also numerically simulated. In-plane compression tests at strain rates around 400/s quasi-isotropic laminates were performed using the Split Hopkinson Pressure Bar (SHPB). The material system used was Texipreg (R) HS160 REM, comprising high strength unidirectional carbon fiber and epoxy resin. The dynamic strength of quasi-isotropic laminates exhibits a considerable increase when compared to the static values. The finite-element model used ABAQUS (TM) three-dimensional solid elements C3D81 with 8 nodes and user-defined interface finite elements with 8 nodes [Gongalves JPM, de Moura MFSF, de Castro PMST, Marques AT. Interface element including point-to-surface constraints for three-dimensional problems with damage propagation. Eng Comp: Int J Comput Aided Eng Software 2000;17(1):28-47; de Moura MFSF, Pereira AB, de Morais AB. Influence of intralaminar cracking on the apparent interlaminar mode I fracture toughness of cross-ply laminates. Fatigue Fract Eng Mater Struct 2004;27(9):759-66.]. These interface elements which connect the three-dimensional solid elements modeling the composite layers, include a cohesive damage model allowing the simulation of delamination initiation and propagation. Hence the present model assumes that the phenomenon of failure under these conditions is mainly dictated by interface delamination. This is supported by experimental tests which showed that all quasi-isotropic laminates split into several almost intact sublaminates. The model compares very well with experimental results, confirming the formulated hypothesis that the internal layer damage does not markedly contribute to the quasi-isotropic laminate failure.